“Ars”: Visual Arts magazine by PPGAV, ECA/University of Sao Paulo - Prado, Gilbertto; Giannotti, Marco; Salzstein, Sônia; Ramiro, Mario; Caecilius Jr., Raul (PORTO ARTE: Revista de Artes Visuais, 2013)
The “Ars” magazine, created by the graduate program in Visual Arts from Escola de Comunicação e Artes [School of Arts and Communication], at the University of Sao Paulo, gathers art relevant works by students at the university and outside of the academia. The magazine suggests that the issues involving an art school should not remain restricted to the academic environment, but should be taken as a cultural debate beyond the University walls and doubt art perspectives in a contemporary context.